SINGLE SESSION BILATERAL PERCUTANEOUS NEPHROLITHOTOMY (PCNL) IN HORSESHOE KIDNEY PATIENT WITH BILATERAL STAGHORN STONES: A CASE REPORT - Dhalas, Rizal Rian; Utomo, Nugroho Budi; Hariyono; Prasaja, Nindra (Indonesian Urological Association, 2024)
Objective: To analyze the outcomes of single-session bilateral PCNL in a horseshoe kidney patient with bilateral staghorn stones in terms of safety and effectiveness. Case(s) Presentation: A 64-year-old woman with bilateral staghorn stones on HSK. She had an anesthesia status of ASA 2, with type 2 diabetes mellitus (uncontrolled with oral medication), 47% of ejection fraction from echocardiography and her body mass index was 21.7 kg/m2. A single session of bilateral PCNL was performed, with 150 minutes of surgery and total blood loss of ± 50 cc. A 4.7 Fr DJ stent was placed on the right kidney, a 5 Fr ureteral catheter was left in the left kidney, and a 16 Fr foley catheter was placed as a right and left nephrostomy. Control plain abdominal x-ray showed no residual stones. Postoperatively, the patient was hospitalized for 3 days, there were no significant complaints and discharged in good condition. Discussion: The procedure was performed in the prone position for two reasons. First, is to avoid intestinal injury during puncture and dilatation, the second is to simplify the positioning of the C arm, as well as the endourology monitor, and the other instruments. Conclusion: Single-session bilateral PCNL for HSK patients with bilateral staghorn stones, in our experience, is quite safe and effective. Keywords: Horseshoe kidney, single-session bilateral percutaneous nephrolithotomy (PCNL), staghorn stone.